Analisis Anggaran Biaya Sebagai Alat Pengendalian Manajemen Pada Kantor Desa Liyodu Kecamatan Bongomeme (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine and analyze the use of budget costs as a management control tool at the Liyodu Village Office, Bongomeme District. The method used in this study is a qualitative method and uses efficiency and effectiveness ratios. The results of the study indicate the ineffectiveness of the budget costs in Liyodu Village in line with the results of previous studies that highlight the importance of more in-depth evaluation and supervision to improve the effectiveness of budget use as a management control tool.